Long-term air pollution exposure and cardiovascular disease risk across cardiovascular-renal-metabolic stages: a nationwide study - Leying Zhao; Cong Zhao; Weiwei Sun; Huijuan Zheng; Yabin Gao; Chan Kam Wa; Qiong Wang; Qingqing Liu; Yaoxian Wang; Zhen Wang (BMC Public Health)
Abstract Background Cardiovascular-renal-metabolic (CKM) syndrome substantially elevates the risk of cardiovascular disease (CVD). Environmental air pollution, especially particulate matter (PM), is a key contributor, yet its long-term effects across CKM stages remain unclear. Objectives This study aimed to evaluate the association between long-term exposure to different sizes of particulate matter (PM1, PM2.5, PM10) and CVD risk across the four stages of CKM syndrome. Methods We conducted a nationwide prospective cohort study using data from the China Health and Retirement Longitudinal Study (CHARLS, 2011–2018), including 5,824 participants aged 45 years or older. CKM stages (0 to 3) were classified according to American Heart Association guidelines. Annual average concentrations of PM1, PM2.5, and PM10 were used to estimate individual exposure. Cox proportional hazards models were used to calculate adjusted hazard ratios (HRs), and population attributable fractions (PAFs) were estimated to assess the burden of air pollution on CVD. Results During a median follow-up of 7 years, participants in the highest exposure group of PM2.5 had significantly increased CVD risk (HR = 2.31, 95% CI: 2.00–2.66). The risk rose progressively with CKM stage, peaking in stage 3 for PM1 (HR = 3.32, 95% CI: 2.24–4.92). PM1 and PM2.5 showed nonlinear exposure–response patterns, with sharply increasing CVD risk at higher concentrations. The highest PAF (~ 38%) occurred in CKM stage 2 under high PM2.5 exposure, indicating substantial burden among intermediate and advanced CKM stages. Among patients with chronic kidney disease, the association was attenuated, potentially due to medication use. Conclusions Long-term exposure to ambient particulate matter significantly increases CVD risk, especially among individuals in advanced CKM stages. Implications These findings support incorporating CKM staging into environmental health risk assessments and highlight the need for targeted cardiovascular screening and pollution control strategies in high-exposure regions. Clinical trial number Not applicable.